Comparison of murderers with recidivists and first time incarcerated offenders from U.S. prisons on psychopathy and identity as a criminal: An exploratory analysis. (July 2017) - Sherretts, Nicole; Boduszek, Daniel; Debowska, Agata; Willmott, Dominic
Abstract: Purpose: Previous research conceptualized murderers as highly callous and self-gratifying individuals, offending as a result of psychopathic tendencies. The current exploration sought to verify whether murderers differ on psychopathy and criminal social identity from recidivistic and first time incarcerated offenders. Methods: The study compared an opportunistic sample of murderers ( n  = 94), recidivists ( n  = 266), and first time offenders ( n  = 118) on criminal social identity (3 factors: cognitive centrality, in-group affect, and in-group ties) and psychopathy (4 factors: callous affect, interpersonal manipulation, erratic lifestyle, antisocial behavior). Results: Recidivists scored significantly higher on cognitive centrality and in-group ties than murderers. Recidivists scored significantly higher than first time incarcerated offenders or murderers on the erratic lifestyle and interpersonal manipulation factors of psychopathy. Additionally, recidivists scored significantly higher on antisocial behavior compared to first time offenders. All three groups of prisoners did not differ in terms of callous affect. Conclusion: Contrary to previous research and media portrayals of homicide perpetration being rooted in psychopathic tendencies such as callous affect, the present findings found no support for such a conceptualization of the crime. Moreover, unsurprisingly, it appears murderers have less developed criminal cognitions than other offending groups. Highlights: We examined whether murderers differ on psychopathy and criminal social identity from other offending groups. Results reveal murderers scored lower on erratic lifestyle and interpersonal manipulation in comparison to recidivists. There was no significant difference between groups on callous affect. Murderers did not display a higher degree of criminal social identity in comparison to other offending groups.